2007
DOI: 10.1097/hjr.0b013e32808621a3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of exercise training on the kinetics of oxygen uptake in patients with chronic heart failure

Abstract: Exercise training improves O2 kinetics in chronic heart failure patients. Both continuous and interval training improve phase I O2-kinetics, but continuous training results in superior improvement of the phase II O2-kinetics, an indirect index of muscle oxidative capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 37 publications
4
43
0
Order By: Relevance
“…This is an important advantage as compared to O 2 onset kinetics, which requires averaging of multiple exercise tests to obtain a reliable assessment in CHF patients (Roditis et al 2007;Kemps et al 2007). Moreover, the determination of s-rec is objective and can be easily integrated in the software of commercially available breath-bybreath respiratory systems.…”
Section: O 2 Recovery Kineticsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is an important advantage as compared to O 2 onset kinetics, which requires averaging of multiple exercise tests to obtain a reliable assessment in CHF patients (Roditis et al 2007;Kemps et al 2007). Moreover, the determination of s-rec is objective and can be easily integrated in the software of commercially available breath-bybreath respiratory systems.…”
Section: O 2 Recovery Kineticsmentioning
confidence: 99%
“…Other variables that are potentially useful for the assessment of training effects include the rates of changes of _ VO 2 during or after a submaximal constant-load test (O 2 onset and recovery kinetics, respectively). Recently, Roditis et al (2007) reported an improvement in O 2 onset kinetics after physical training in CHF patients. A limitation of their approach, however, was that multiple exercise tests were required to obtain a sufficient signal to noise ratio.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Naturally, concern is warranted for higher-risk patients because higher intensities are used with interval training. Nonetheless, interval training has now been used successfully in several clinical populations, including the elderly (> 75 years) and patients with peripheral artery disease, intermittent claudication, coronary artery disease, COPD, and T2D, without adverse medical side effects or complications [16,24,27,[33][34][35][36][37][38]. Although interval training may not be useful for all patients, the training model does present new alternatives for patients with metabolic complications.…”
Section: Discussionmentioning
confidence: 99%
“…In CHF, different methods have been used to determine these workloads, resulting in variations in the exercise dose. Some studies follow the traditional method of applying workloads of 100% VO 2peak work rate [11,12]. [6,13].…”
Section: Introductionmentioning
confidence: 99%